2017
DOI: 10.1016/j.jad.2017.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing quality of life among adolescents with bipolar disorder: A randomized trial of two psychosocial interventions

Abstract: Background Adolescents with bipolar disorder (BD) report lower quality of life (QoL) than adolescents with other psychiatric disorders. This study compared the efficacy of family-focused therapy for adolescents (FFT-A) plus pharmacotherapy to brief psychoeducation (enhanced care, or EC) plus pharmacotherapy on self-rated QoL in adolescents with BD over 2 years. Methods Participants were 141 adolescents (mean age: 15.6 ± 1.4yr) with BD I or II who had a mood episode in the previous 3 months. Adolescents and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Consistent with prior research [7], it is not surprising that a higher level of emotional problems at baseline was associated with lower initial QoL. Although there have been few longitudinal studies assessing QoL change in adolescent psychiatric patients during and following treatment [49][50][51], they all have reported an increase in QoL over time. In these studies, a single specific structured therapeutic intervention was evaluated.…”
Section: Discussionsupporting
confidence: 68%
“…Consistent with prior research [7], it is not surprising that a higher level of emotional problems at baseline was associated with lower initial QoL. Although there have been few longitudinal studies assessing QoL change in adolescent psychiatric patients during and following treatment [49][50][51], they all have reported an increase in QoL over time. In these studies, a single specific structured therapeutic intervention was evaluated.…”
Section: Discussionsupporting
confidence: 68%
“…In an adolescent sample conducted in three sites, we reported that (1) FFT and a brief family educational treatment (enhanced care, or EC) did not differ on time to recovery from index study episodes or time until recurrence; (2) patients in FFT-A had greater improvements in manic but not depressive symptoms compared to those in EC in the post-treatment year; and (3) patients with comorbid anxiety disorders and ADHD had earlier mood recurrences, regardless of treatment condition (Miklowitz et al, 2014). A separate report from this study found that FFT-A was associated with greater improvements in self-reported quality of life compared to the EC treatment (O'Donnell et al, 2017). However, these studies did not investigate the role that comorbid disorders may play in moderating the effects of family interventions.…”
Section: Introductionmentioning
confidence: 74%
“…Involving the family, O’Donnell and colleagues (2017) tested the effect of 2 psychological interventions on QoL scores in a sample of adolescents with BD. They compared the efficacy of a FFTplus pharmacotherapy vs brief psychoeducation plus pharmacotherapy on self-related QoL over 2 years.…”
Section: Personal Recovery: Well-being and Qolmentioning
confidence: 99%